Ibn Khaldun Economic Thought: A Literature Review and Bibliometric Analysis - Miskal Kholiq; Muhammad Fikriiadi; Muhammad Sahnan (Islamic Economics and History, 2022)
This study aims to find the relevance of Ibn Khaldun's theory of economic thought to modern economic theory where the focus of this research is Ibn Khaldun's micro and macroeconomic theory and its relevance to modern economic theory. This study uses the literature study method by studying literature related to Ibn Khaldun's micro and macroeconomic theories. Apart from using literature study, this research also uses bibliometric mapping using VOSviewer software where the keywords most often searched for in Ibn Khaldun's economic thinking arephilosophy, humanitites, political science, mathematics, history andeconomic thougt. The results of this study indicate that Ibn Khaldun's micro and macroeconomic theories are still relevant to modern economic theory today.